Agents and their actions - De Gaynesford, Maximilian; Wiley InterScience (Online service) (Chichester, UK ; Malden, MA : Wiley-Blackwell, 2011)
"Reflecting a recent flourishing of creative thinking in the field, Actions and Their Agents presents seven newly commissioned essays by leading international philosophers that highlight the most recent debates in the philosophy of action Features seven internationally significant authors, including new work by two of philosophy's 'super stars', John McDowell and Joseph Raz Presents the first clear indication of how John McDowell is extending his path-breaking work on intentionality and perceptual experience towards an account of action and agency Covers all the major interconnections between action-agency and central areas of Philosophy: Metaphysics, Epistemology, History of Philosophy, Ethics, Logic, Philosophy of Language Provides a snapshot of current debate on the subject, which is fresh, enlightening, and fruitful"--
Front Matter -- Reasons for Action and Practical Reasoning / Maria Alvarez -- Ambivalence and Authentic Agency / Laura W Ekstrom -- The Road to Larissa / John Hyman -- What is the Content of an Intention in Action? / John McDowell -- Being in the World / Joseph Raz -- Moral Scepticism and Agency: Kant and Korsgaard / Robert Stern -- Speech, Action and Uptake / Maximilian de Gaynesford -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Act (Philosophy); Agent (Philosophy); PHILOSOPHY -- History & Surveys -- General; Act (Philosophy); Agent (Philosophy); Electronic books; Electronic resource